Predictors of occupational sensitisation to grain dust allergens and changes in lung function among grain mill workers in Cape Town - Jeebhay, Mohamed Fareed (Institute of Infectious Disease and Molecular Medicine, 2017)
Occupationally-related airway diseases, including asthma and chronic obstructive lung disease, have emerged as having substantial public health importance. The aim of this study was to identify the predictors of occupational sensitisation to grain dust allergens and changes in lung function among grain mill workers in Cape Town. There were two major objectives of the study. Firstly, to determine which of the following factors determine the distribution of serum ECP (eosinophilic cationic protein): age, gender, grain dust exposure, smoking status, atopy and sensitisation to workplace allergens. Secondly, to investigate the risk factors associated with the following outcomes: i) sensitisation to occupational allergens; ii) diagnosis of occupational asthma; iii) diagnosis of chronic obstructive airways disease; and iv) longitudinal changes in lung function. The risk factors studied included age, gender, smoking habits, occupational exposure, lung function status on baseline survey (1989), and allergic sensitisation assessed at follow up (1996). The methods employed involved a repeat measures cross-sectional design including a cohort followed up at different points over a seven year period. Survey instruments included a questionnaire, spirometry and allergy tests (phadiotop, RAST for wheat, rye, Lepidoglyphus destructor, Tyrophagus putrescentiae and Sitophilus granarius). The results indicated an association of grain dust with pulmonary function and allergic sensitisation to grain dust constituents. After adjusting for known confounders such as age, gender and smoking, significant associations were found between employment duration and both decrements in lung function and sensitisation to wheat grain. A decrement of 278 ml in FEY 1 and 328 ml in FYC was associated with occupational sensitisation to wheat (and rye). Increasing employment duration resulted in annual decrements of 18.3 ml in FEY1 and 23 ml in FYC for every year employed. The odds for developing occupational asthma was only mildly elevated (OR=l.35) with increasing employment duration. Age, however, was found to be protective (OR=0.85). Although we were unable to demonstrate a relationship between across-week changes in lung function, at inception, and rapid longitudinal lung function decline, our findings suggested that longitudinal change was related to the degree of airway obstruction at inception. Sensitisation to grain dust allergens was also found to be an independent predictor for FEY 1 and FYC. The prevalence of sensitisation was the highest for wheat (26.4%), followed by Tyrophagus putrescentiae (22.6%), rye (21.7%), Lepidoglyphus destructor (15.1 %) and Sitophilus granarius (15.1 %). Sensitisation to wheat was highly correlated with sensitisation to rye (r = 0.92) and so were Lepidoglyphus destructor and Tyrophagus putrescentiae (r = 0.85). Although a large proportion of the workforce ( 41.5 % ) were sensitised to occupational allergens, the prevalence of respiratory symptoms was between 15.6% and 23.9%. There were 16.7% of workers with health outcomes which fulfilled our criteria for occupational asthma. Atopic workers in our study had at least a nine-fold increased odds of becoming sensitised to grain dust allergens (OR: 8.9-74.7) and a two-fold increased odds of developing occupational asthma (OR= 1.9-84.9). Furthermore, the study found that smokers had a twofold increased odds of becoming atopic, thereby placing them at greater risk of developing respiratory health problems. The mean ECP in this population was 15.4 ug/1 (SD:2.5). Although 45.3% of the workers were atopic, it was not found to be predictor of elevated ECP levels. We were however able to demonstrate a significant association between ECP and sensitisation to grain allergens. Workers sensitised to wheat (positive RAST) had, on average, 1. 78 ug/1 higher ECP levels. The odds of having an elevated ECP (> 15 ug/1) increased by 2.9 for workers sensitised to wheat grain. In conclusion, the results of the study indicate that selection effects are in operation, demonstrating the health worker effect. The findings also suggest that across week reactions may be less sensitive than the across shift changes in predicting rapid longitudinal decline in lung function. While we were able to characterise the distribution of ECP according to exposure, we were however unable to define the temporal relationship between elevated between exposures, ECP and lung function outcomes due to limitations of the study design.